State social protection of persons with disabilities, the scientific and theoretical context - Мельник, Володимир Петрович (Київський національний університет імені Тараса Шевченка, 2017)
This article examines the features of social protection of persons with disabilities. Theattention to its constitutional and legal nature is paid. It is noted about certain problems in thefunctioning of social protection of persons with disabilities. The scientific and theoreticalaspects of the above mentioned issues are highlighted. The trend of formation of Ukraine publicsocial protection of persons with disabilities is emphasized. Conclusions and suggestions aregiven.

инвалидностью. Акцентируется внимание на его конституционно-правовойприроде, отмечаются проблемы функционирования государственной социальнойзащиты лиц с инвалидностью, указывается на научно-теоретические аспектыизлагаемой проблематики, подчеркивается тенденция формирования в Украинепубличной социальной защиты лиц с инвалидностью, сделаны выводы и предложения.
Державний соціальний захист осіб з інвалідністю: науково-теоретичний контекст
Keywords: invalidity; a person with a disability; the social protection; state social protection; state social protection bodies; local authorities social protection; National budget; local budgets.; інвалідність; особа з інвалідністю; соціальний захист; державний соціальний захист; державні органи соціального захисту; місцеві органи соціального захисту; державний бюджет; місцеві бюджети.